The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1021/acs.nanolett.6b05087
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-Confined and Enhanced Optical Absorption of Colloidal PbS Quantum Dots at Wavelengths with Expected Bulk Behavior

Abstract: Nowadays it is well-accepted to attribute bulk-like optical absorption properties to colloidal PbS quantum dots (QDs) at wavelengths above 400 nm. This assumption permits to describe PbS QD light absorption by using bulk optical constants and to determine QD concentration in colloidal solutions from simple spectrophotometric measurements. Here we demonstrate that PbS QDs experience the quantum confinement regime across the entire near UV−vis−NIR spectral range, therefore also between 350 and 400 nm already pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 28 publications
6
50
1
Order By: Relevance
“…In this context, most of the studies focus on the influence of ligands on the optoelectronic properties of NCs [30][31][32][33][34][35][36][37] . In particular, somespecific surface modifications with organic ligands proved to enhance light absorption and fluorescence emission [38][39][40] , which is a clear advantage for photovoltaic, photodetection and photoemission applications. It has also been shown that ligands condition the quantum confinement and the phonon behaviour of NCs, thus affecting exciton dynamics and transport phenomena [41][42][43] .…”
mentioning
confidence: 99%
“…In this context, most of the studies focus on the influence of ligands on the optoelectronic properties of NCs [30][31][32][33][34][35][36][37] . In particular, somespecific surface modifications with organic ligands proved to enhance light absorption and fluorescence emission [38][39][40] , which is a clear advantage for photovoltaic, photodetection and photoemission applications. It has also been shown that ligands condition the quantum confinement and the phonon behaviour of NCs, thus affecting exciton dynamics and transport phenomena [41][42][43] .…”
mentioning
confidence: 99%
“…In addition, Murphy et al reported the large anisotropy inherent to the bandstructure of PbTe (a B ∼ 12 nm, a B⊥ ∼ 152 nm), which is most pronounced among the lead chalcogenide systems, compared to 66 nm for PbSe and 23.5 nm for PbS [29]. Therefore, our synthesized PbTe NRs with different lengths may present quantum-confinement effects in three dimensions and reveal how their anisotropic properties affect the optoelectronic properties of PbTe NCs [41]. In the near infrared region, the first excitonic absorption peak of PbTe NRs red-shifts from 1182 to 1713 nm as the average diameter of corresponding NRs increases from 2.8 to 5.4 nm (Fig.…”
Section: Impact Of Growth Temperature On Pbte Nrsmentioning
confidence: 70%
“…Quantum connement of carriers and enhanced surface effects at nanodimensions are well known to result in large modications in the structural, optical, and electronic properties of nanoparticles. 38,39 Balamurugan B. has reported the sizedependent changes in Cu 2 O nanoparticles, result in conductivity type inversion on reduction of nanoparticle size. [40][41][42] So it is necessarily to know how and what is the extent the quantum connement of Cu 2 S effect on the visible light catalytic performance.…”
Section: Resultsmentioning
confidence: 99%